Collateral framework: Liquidity premia and multiple equilibria - Yvan Lengwiler; Athanasios Orphanides (University of Basel, Center of Business and Economics (WWZ), 2021)
Central banks normally accept debt of their own governments as collateral in liquidity operations without reservations. This gives rise to a valuable liquidity premium that reduces the cost of government finance. The ECB is an interesting exception in this respect. It relies on external assessments of the creditworthiness of its member states, such as credit ratings, to determine eligibility and the haircut it imposes on such debt. We show how such features in a central bank's collateral framework can give rise to cliff effects and multiple equilibria in bond yields and increase the vulnerability of governments to external shocks. This can potentially induce sovereign debt crises and defaults that would not otherwise arise.
Keywords: E58; E62; E43; 330; monetary policy; government finance; yields; liquidity premium; default premium; collateral; cliff effect; multiple equilibria